Dispersion-engineered nanocomposites enable achromatic diffractive optical elements - Werdehausen, Daniel; Burger, Sven; Staude, Isabelle; Pertsch, Thomas; Decker, Manuel (Optica, 2019)
The use of diffractive optical elements (DOEs) in broadband optical systems can often significantly reduce their size or enhance their performance but is mostly prevented by stray light in unwanted diffraction orders. This is because dispersion causes the diffraction efficiency to decrease as a function of the wavelength. Here we introduce nanocomposites as a material platform that allows for the design of dispersion-engineered materials. We show that these materials enable the design of almost dispersion-free, i.e., achromatic, echelette-type gratings with diffraction efficiencies of close to 100% in the entire visible spectral range. Using numerical simulations, we demonstrate that such high efficiencies are maintained across the range of incidence angles and grating periods required for most optical systems. This concept of dispersion-engineered nanocomposites can also be applied to other applications, and nanocomposite-enabled DOEs have the potential to be an enabling technology for a new generation of better and more compact optical systems.
CRIS-Team Scopus Importer:2023-04-20